CLINICO PATHOLOGICAL STUDY AND MOLECULAR DETECTION OF IBD INFECTED BROILERS IN BASRAH PROVINCE - Dheyaa abbas abdali; Waleed Majeed Seger Almayahi (Basrah Journal of Veterinary Research)
IBD is a highly contagious viral disease which inhibit the immune system ofchickens, which is responsible for major economic losses within the poultry industriesworldwide. A total of 80 samples were collected from 8 different broiler farms fromQurna, Midyanah, Qarmat Ali, Zubair. Upon the clinical finding and postmortemlesions of the necropsied birds; bursa of fabricius, kidney, Junction between gizzardand proventriculus and thigh muscles were processed for histopathological andmolecular detection with PCR. The clinical signs were depression, pasty vent andwhite dropping. Various overall changes are observed in the bursa, such as swelling,hemorrhages to atrophy in size; In addition, hemorrhages were seen in the thighmuscles. The histopathological changes of Bursa of fabricius showed follicularvacuolation and vascular congestion ;multiples degrees of hemosiderin deposition,and the edema accumulate between follicles and basement membrane ; also, showedmoderate infiltration of inflammatory cells and accumulation of inflammatory cellslymphocytes macrophage , plasma cells as well to showed a congestion of the bursalcapsule, kidney microscopic findings renal vascular congestion in the cortex and alsothe medullary area along with the vacuolar degeneration. The suspected tissuesamples were assayed using RT-PCR for IBDV targeting VP2 gene. Out of the testedsamples 15 were Positives. In spite of using IBD vaccines in different farms of thestudied areas; the present study was detected IBD in different areas of Basrahprovince by PCR and mentioned clinical and histopathological finding, therefore it'snecessary to study the sequence analyses of such disease in future.